Holocene Aeolian Activity Recorded by Mountain Paleosols, Gonghe Basin, Northeast Qinghai-Tibet Plateau - Xu, Chunxia; E, Chongyi; Shi, Yunkun; Zhang, Jing; Sun, Manping; Zhang, Zhaokang; Zeng, Yongxin (Frontiers in Earth Science, 2022)
The Gonghe Basin (GHB) on the northeastern Qinghai-Tibet Plateau (NE-QTP) is sensitive to climatic change due to the interplay of the Asian summer monsoon and the westerlies. Extensive aeolian sediments in the basin represent important archives of regional environmental evolution. However, the paleosol development timing is still not clear because of limited number of optically stimulated luminescence (OSL) sampling and dating, which restricts our understanding of past aeolian activities during the Holocene in GHB. In this study, a loess-paleosol section, Najiao (NJ), from the southeastern margin of GHB was investigated. Eighteen OSL samples were obtained from the 400-cm section in order to construct a high-resolution chronological framework. Paleoenvironmental proxies including grain size distribution (GS), magnetic susceptibility (MS), total organic carbon (TOC), and geochemical elements were measured to reconstruct the Holocene aeolian activity. Results show a successive accumulation from Early to Middle Holocene at NJ section, but a c. 3 ka sedimentary hiatus is found between c. 5 and 1.5 ka. Paleosol ages are constrained by high-resolution OSL ages which are from c. 7–5 ka. Consistent with previous studies, strong aeolian activities occurred in GHB during the Early Holocene (c. 13–9 ka), indicating dry climate conditions. Initiation of pedogenesis was at c. 9 ka, and the intensified soil development and lowest aeolian activity were between c. 7 and 5 ka. The increased sand content after c. 1.5 ka indicates enhanced human activities in the interior of GHB in the Late Holocene.